2009
DOI: 10.1111/j.1440-0960.2009.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoxanthoma elasticum‐like lesions in association with thalassaemia major

Abstract: A 33-year-old woman with a background of thalassaemia major presented with a 3-month history of yellowish plaques on the back of her neck bilaterally and alterations in the texture of the skin in both axillae. Examination of these lesions showed yellowish cobblestone plaques and coalescing papules in both axillae. Pseudoxanthoma elasticum (PXE)-like lesions were confirmed histopathologically. PXE-like lesions in association with thalassaemia major are an uncommon occurrence. Due to the increase in the survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…IgG autoantibodies reacted with a recombinant form of collagen VII by enzyme-linked immunoassay. 1 The digital dental radiographs revealed the presence of all permanent tooth buds intramaxillary with no evidence for dysplastic disorders of the hard dental tissues. Based on clinical, histopathological and immunological findings, the diagnosis of epidermolysis bullosa acquisita (EBA) was established.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…IgG autoantibodies reacted with a recombinant form of collagen VII by enzyme-linked immunoassay. 1 The digital dental radiographs revealed the presence of all permanent tooth buds intramaxillary with no evidence for dysplastic disorders of the hard dental tissues. Based on clinical, histopathological and immunological findings, the diagnosis of epidermolysis bullosa acquisita (EBA) was established.…”
mentioning
confidence: 94%
“…1 Pseudoxanthoma elasticum-like lesions have been described in hemoglobinopathies, for example, sickle-cell disease (SCD) and thalassemia, mainly in beta-thalassemia. 2 The clinical presentation, histopathology, ultrastructure and immunochemistry of PXE-like lesions are similar to inherited PXE, but with no ABCC6 mutation.…”
mentioning
confidence: 99%
“…Cianciulli et al 10 describen afectació n cutá nea en el 17% de pacientes con beta-talasemia. Las alteraciones del colá geno, así como la fragmentació n y mineralizació n de las fibras elá sticas, eran estructuralmente idé nticas a las observadas en la forma hereditaria, hallazgos coincidentes con los de otros trabajos publicados [16][17][18][19] . El largo seguimiento del estudio mostró que las lesiones PXE-like no parecían relacionadas con la severidad de la anemia, la duració n de las tranfusiones sanguíneas, la esplenectomía, ni con el historial de quelació n 10 .…”
Section: Discusió Nunclassified
“…PXE-like symptoms are associated with certain cases of haemoglobinopathy, including ␤ -thalassaemia and sicklecell disease [5][6][7][8]. A systematic study of 100 patients with thalassaemia in Greece showed that 16% had PXE cutaneous lesions and 10% had both PXE lesions and angioid streaks [5].…”
Section: Pseudoxanthoma Elasticum-like Skin Lesions With Congenital Ementioning
confidence: 99%
“…In another study, 14 of 80 ␤-thalassaemia patients had PXE-like skin lesions with elastic fiber fragmentation and calcification [6]. In ␤-thalassaemia, unbound fractions of globin and heme are presumed to result in high levels of oxidative stress, which may cause elastic tissue injury [7]. Furthermore, iron overload by repeated blood transfusions can markedly damage elastic fibers in tissue [8].…”
Section: Pseudoxanthoma Elasticum-like Skin Lesions With Congenital Ementioning
confidence: 99%